2012
DOI: 10.1038/ng.1105
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous missense mutations in SMARCA2 cause Nicolaides-Baraitser syndrome

Abstract: Nicolaides-Baraitser syndrome (NBS) is characterized by sparse hair, distinctive facial morphology, distal-limb anomalies and intellectual disability. We sequenced the exomes of ten individuals with NBS and identified heterozygous variants in SMARCA2 in eight of them. Extended molecular screening identified nonsynonymous SMARCA2 mutations in 36 of 44 individuals with NBS; these mutations were confirmed to be de novo when parental samples were available. SMARCA2 encodes the core catalytic unit of the SWI/SNF AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
209
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(211 citation statements)
references
References 25 publications
1
209
0
1
Order By: Relevance
“…Some studies have revealed that Smarca4 is essential for heart development in mouse and zebrafish embryogenesis, whereas Smarca2 appears to be dispensable 34,35 . In humans, the role of SMARCA2 in cardiogenesis is unclear; however, several independent exome sequencing projects have identified de novo mutations in SMARCA2 that are associated with two congenital syndromes that include cardiac defects: Coffin-Siris syndrome and Nicolaides-Baraitser syndrome 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have revealed that Smarca4 is essential for heart development in mouse and zebrafish embryogenesis, whereas Smarca2 appears to be dispensable 34,35 . In humans, the role of SMARCA2 in cardiogenesis is unclear; however, several independent exome sequencing projects have identified de novo mutations in SMARCA2 that are associated with two congenital syndromes that include cardiac defects: Coffin-Siris syndrome and Nicolaides-Baraitser syndrome 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, heterozygous nonsynonymous mutations or partial deletions in SMARCA2 were identified as the cause of Nicolaides-Baraitser syndrome, an autosomal dominant condition with syndromic ID. 30 The third probably causal abnormality was a de novo deletion on chromosome 3q29. The 3q29 microdeletion syndrome has been recently described as a new syndrome, probably caused by nonallelic homologous recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Patients NL39 and NL66 both had a CNV in chromosomal band 9p24.3. The smallest overlap region contained a single gene, SMARCA2, which has recently been associated with Nicolaides-Baraitser syndrome 14 ( Supplementary Figure 2). However, duplications in other parts of this gene have been found as benign variants, raising issues regarding the pathogenicity of these variants.…”
Section: Novel Recurrent Cnvsmentioning
confidence: 99%